STUDI CROSS-SECTIONAL: HUBUNGAN LOKASI SEKOLAH (PEDESAAN DAN PERKOTAAN) DENGAN STATUS GIZI MURID SEKOLAH DASAR - Kushargina, Rosyanne; Dainy, Nunung Cipta (JURNAL RISET GIZI, 2021)
Background: Adequate nutrition plays an important roles for children on school age to developed and maintain their growth and health. Many factors could affect the nutritional status of school children, one of them is the school location.Objectives: To analysis the correlation between school location with nutritional status of elementary school students.Method: The research design used was a cross-sectional design. 80 subjects were observed from two different schools namely SDN 1 Cikelet Garut (Urban) and SDN Pesanggrahan 02 Pagi Jakarta Selatan (Rural). The relationship of school location and gender with nutritional status were analyzed using Chi Square. Independent Sample T-test used to analyze nutritional status based on different locations.Result: In rural there are 25% of children with over nutritional status (weight/age). There are still stunted child both in urban (7.50%) and rural (10%), but based on weight/height nutritional status, almost all subjects in both urban (92.50%) and rural (97.50%) in obese category. Chi Square analysis showed that the school location was significantly related (P <0.05) only with the weight/age nutritional status. Gender is significantly related to height/age nutritional status. The majority of boys (15,4%) are shorter than girls (2,4%). The results of the Independent Sample T-test based on location, showed that the nutritional status of subjects in urban was significantly different (P<0.05) from the nutritional status of subjects in rural. In line with this, based in gender there is significantly different (P<0.05) in nutritional status between boy and girl.Conclusions: The results of this study indicate that differences in school locations are related to the nutritional status of elementary school students.